Accessing habitats first helps less when your competitors themselves have help. Issue 2 (April 2015) - Tanentzap, Andrew J.
Abstract Species that arrive early into a new habitat influence the interspecific interactions of later arrivals, thereby shaping the structure, functioning and evolutionary potential of biological communities. Burkle & Belote (Applied Vegetation Science, this issue) show that the advantage conferred to pioneer species by earlier access is reduced in the presence of soil mutualists, offering important lessons for restoration.